Core-binding factors in hematopoiesis and immune function. - de Bruijn, M; Speck, N (2004)
Core binding factors are heterodimeric transcription factors containing a DNA binding Runx1, Runx2, or Runx3 subunit, along with a non DNA binding CBF beta subunit. All four subunits are required at one or more stages of hematopoiesis. This review describes the role of Runx1 and CBF beta in the initiation of hematopoiesis in the embryo, and in the emergence of hematopoietic stem cells. We also discuss the later stages of hematopoiesis for which members of the core binding factor family are required, as well as the recently described roles for these proteins in autoimmunity.